Saccharomyces cerevisiae cell surface display technology: Strategies for improvement and applications - Zhang, Chenmeng; Chen, Hongyu; Zhu, Yiping; Zhang, Yu; Li, Xun; Wang, Fei (Frontiers in Bioengineering and Biotechnology, 2022)
Microbial cell surface display technology provides a powerful platform for engineering proteins/peptides with enhanced properties. Compared to the classical intracellular and extracellular expression (secretion) systems, this technology avoids enzyme purification, substrate transport processes, and is an effective solution to enzyme instability. Saccharomyces cerevisiae is well suited to cell surface display as a common cell factory for the production of various fuels and chemicals, with the advantages of large cell size, generally recognized as safe (GRAS), and post-translational processing of secreted proteins. In this review, we describe various strategies for constructing modified S. cerevisiae using cell surface display technology and outline various applications of this technology in industrial processes, such as biofuels and chemical products, environmental pollution treatment, and immunization processes. The approaches for enhancing the efficiency of cell surface display are also discussed.